Frailty, body composition and the risk of mortality in incident hemodialysis patients: the Predictors of Arrhythmic and Cardiovascular Risk in End Stage Renal Disease study. Issue 2 (4th June 2018) - Fitzpatrick, Jessica; Sozio, Stephen M; Jaar, Bernard G; Estrella, Michelle M; Segev, Dorry L; Parekh, Rulan S; McAdams-DeMarco, Mara A
Abstract: Background: Frail obese community-dwelling older adults are at increased mortality risk. Among hemodialysis (HD) patients, frailty is common and associated with increased mortality risk; however, in dialysis, obesity is associated with decreased mortality risk. Whether the frail–obese phenotype is associated with increased mortality risk among HD patients remains unclear. Methods: This study included 370 incident HD patients enrolled in the Predictors of Arrhythmic and Cardiovascular Risk in End Stage Renal Disease (PACE) study. We measured frailty using the Fried phenotype, general obesity [body mass index (BMI) ≥30 kg/m 2 ] and abdominal obesity [waist:hip ratio (WHR) ≥median WHR] and estimated their associations with mortality. Results: The mean age was 55 years, with 42% female, 73% African American, 57% diabetic and 52% frail. Frail HD patients had higher mean BMI (frail = 30.3 kg/m 2, non-frail = 28.3 kg/m 2 ; P = 0.02) and similar WHR (P = 0.8). Twenty-two percent were frail with general obesity and 27% were frail with abdominal obesity. Frailty was associated with 1.66-fold increased mortality risk [95% confidence interval (CI) 1.03–2.67]. BMI was associated with a decreased mortality risk [25.0–29.9 kg/m 2 hazard ratio (HR) 0.53 (95% CI 0.31–0.93); ≥30 kg/m 2 HR 0.34 (95% CI 0.19–0.62)]. Frailty was associated with elevated mortality risk among HD patients with general [HR 3.77 (95% CI 1.10–12.92)] and abdominal obesity [HR 2.38 (95% CI 1.17–4.82)]. Frailty was not associated with mortality among HD patients without general or abdominal obesity. Conclusions: In adults initiating HD, frailty was associated with elevated mortality risk, even among the obese. Frail–obese HD patients may be a high-risk, often-overlooked population, as obesity is assumed to be protective. Measurement of frailty and obesity may facilitate risk stratification.